The relationship between indicators of socioeconomic status and cesarean section in public hospitals - Alexandre Faisal-Cury (Revista de Saúde Pública, 2017)
OBJECTIVE: To assess the relationship between indicators of socioeconomic status and cesarean section in public hospitals that adopt standardized protocols of obstetrical care. METHODS: This was a prospective cohort study conducted between May 2005 and January 2006 with 831 pregnant women recruited from 10 public primary care clinics in São Paulo, Brazil. Demographic and clinical characteristics were collected during pregnancy. The three main exposures were schooling, monthly family income per capita , and residential crowding. The main outcome was cesarean section at three public hospitals located in the area. Crude and adjusted risk ratios (RR), with 95% confidence intervals were calculated using Poisson regression with robust variance. We examined the effects of each exposure variable on cesarean section accounting for potential confounders by using four different models: crude, adjusted by mother’s characteristics, by obstetrical complications, and by the other two indicators of socioeconomic status. RESULTS: Among the 757 deliveries performed in the public hospitals, 215 (28.4%) were by cesarean section. In the bivariate analysis, cesarean section was associated with higher family income per capita , higher education, lower residential crowding, pregnancy planning, white skin color, having a partner, and advanced maternal age. In the multivariate analysis, after adjustment for covariates, none of the socioeconomic status variables remained associated with cesarean section. CONCLUSIONS: In this group, the chance of women undergoing cesarean section was not associated with indicators of socioeconomic status only, but was defined in accordance with major obstetric and clinical conditions.